The different system with preventive maintenance and repair - G.S, Mokaddis; Alhajeri, Hana’a (Opción, 2020)
The study aims to investigate different systems with preventive maintenance and repair. The system is analyzed by the semi-Markov process technique, to solving the equations by using Laplace transformation for integral equations. As a result, it is better to use preventive maintenance under the system I because the mean lifetime of the system under this system is greater than the mean lifetimes for the system under system III and II. In conclusion, the meantime for the system with repair and preventive maintenance is greater than the meantime for the system with a repair only can be proved.